Solar Drying and Sensory Attributes of Eland (Taurotragus oryx) Jerky - Iva Kučerová; Štěpán Marek; Jan Banout (Journal of Food Quality)
A double-pass solar drier (DPSD) and a laboratory oven (LO) were used for thin-layer drying of eland and beef. Prior to drying, the physicochemical characteristics of the raw meat were determined, such as pH, dry matter content (%), Warner-Bratzler shear force (N), pigment concentration (mg·kg−1), weight loss during cooking (%), water holding capacity (%), colour (L,a,b), and crude fat content (%). Both meats were pretreated with traditional jerky marinade (TM), TM with fresh pineapple juice (TMP), TM with honey (TMH), and TM with Coca Cola© (TMCCL) and compared to an untreated control (C). The sensory properties of the eland and beef jerky were assessed in a two-stage process. The surface colour values of the jerky samples were measured in the CIE L⁎  a⁎  b⁎ colour space and the effect of the different pretreatments on the overall combined colour (ΔE) was calculated. Significant differences (p<0.05) between raw eland and beef samples were found in case of pH, pigment concentration, water holding capacity, crude fat content, and colour (L and b). Jerky from TMP pretreated meat had the highest scores for texture, colour, and taste. Generally, for both meats dried in both driers, TMH marinade was evaluated as the one with the highest total difference ΔE compared to meat dipped in TMP pretreatment, which had the lowest total difference ΔE.